2014
DOI: 10.1002/elan.201400392
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Trace Levels of Chromium with Bismuth Modified Pyrolyzed Photoresist Carbon Electrodes

Abstract: Pyrolyzed photoresist carbon electrodes modi-\ud fied with bismuth (Bi-PPCEs) were prepared and used\ud for the determination of trace levels of chromium. In\ud order to lower the detection limit, the choice of the sup-\ud porting electrolyte concentration and electroanalytical pa-\ud rameters were optimized. The adsorptive cathodic strip-\ud ping voltammetric determination of Cr(VI) at Bi-PPCE\ud was selective even in the presence in Cr(III). A detection\ud limit of 0.1\ud m\ud gL\ud \ud 1\ud was obtained aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The main benefit of PPFs is their very high smoothness and the possibility to pattern the film before pyrolysis by photolithography. This PPF material has also been considered in [140,141] to build in-situ or ex-situ Bi-modified pyrolyzed photoresist carbon electrodes for the determination of Ni(II) and Cr(VI) by AdSV using as complexing ligands DMG and pyrocatechol violet, respectively. Moreover, the use of graphene functionalized with negatively charged poly(sodium 4-styrene sulfonate) (PSS) improves the sensitivity and linearity of the analysis of Pb(II) and Cd(II) creating more adsorbing sites [142].…”
Section: Bismuth Electrodesmentioning
confidence: 99%
“…The main benefit of PPFs is their very high smoothness and the possibility to pattern the film before pyrolysis by photolithography. This PPF material has also been considered in [140,141] to build in-situ or ex-situ Bi-modified pyrolyzed photoresist carbon electrodes for the determination of Ni(II) and Cr(VI) by AdSV using as complexing ligands DMG and pyrocatechol violet, respectively. Moreover, the use of graphene functionalized with negatively charged poly(sodium 4-styrene sulfonate) (PSS) improves the sensitivity and linearity of the analysis of Pb(II) and Cd(II) creating more adsorbing sites [142].…”
Section: Bismuth Electrodesmentioning
confidence: 99%
“…Pyrolyzed photoresist films were obtained by the annealing of AZ5214E photoresist at temperatures above 1000 °C, which is higher than what can be generally found in literature [2][3][4][5]. PPF layers have been synthetized by spin coating depositing on SiC of AZ5214E photoresist film with a thickness of approximately 1 µm.…”
Section: Methodsmentioning
confidence: 99%
“…Discovered in 1984, fourteen years later, PPF has been used as a working electrode [2], showing interesting properties in terms of durability and reliability. Nowadays, PPF is used in research as a biocompatible working electrode for electrochemical analysis [3], or as a sensitive and selective electrode for heavy metals detections [4]. Del Campo et al also showed the possibility to include PPF in CMOS technology [5].…”
Section: Introductionmentioning
confidence: 99%
“…Then due to environmental concerns of mercury, methods using bismuth-based electrode [21,22] and other alternative electrodes have been developed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%